The Long-Term Effect of Blue-Light Blocking Spectacle Lenses on Adults’ Contrast Perception - Lian, Yan; Lu, Weiwei; Huang, Haixiao; Wu, Ge; Xu, Aiqin; Jin, Wanqing (Frontiers in Neuroscience, 2022)
Purpose: To evaluate the long-term effect of two different degrees of blue-light blocking (BB) spectacle lenses on adults’ contrast perception under various lighting conditions. Methods: 144 healthy adults aged 24.70 (± 4.32 years) were recruited to this randomized controlled trial. The participants were randomly divided into three groups and used three different spectacle lenses (15% BB: 15% blue-blocking spectacle lenses; 30% BB: 30% blue-blocking spectacle lenses; RC: regular clear lenses serving as control). Contrast sensitivity under four light conditions (scotopic and photopic, both with/without glare) was measured using standard clinical tests at baseline, 1 month, 3 months and 6 months of use. The area under the log contrast sensitivity function (AULCSF) was also computed as an index for their overall contrast sensitivity across spatial frequencies. Results: There was no significant difference in AULCSFs among the three types of spectacle lenses under any light condition (all P > 0.81). No statistical difference was found in the AULSCF among the four time points (all P > 0.39), with no interaction between the effects of group and time (all P > 0.42). Conclusions: Wearing blue-light blocking lens had no clinically significant effect on adults’ long-term contrast perception under scotopic or photopic conditions, or with glare.